Pentingnya Membangun Kesadaran Lingkungan Melalui Pembelajaran PKN di Sekolah Dasar dalam Membentuk Karakter pada Siswa - Subhan; Prof. Dr. Dewa Bagus Sanjaya, M.Si; Prof. Dr. I Nengah Suastika, M. Pd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Civic Education (PKN) in elementary schools plays a strategic role in shaping students' environmental care character. Integrating environmental values into the curriculum can be an effective tool in raising students' awareness and responsibility towards environmental conservation. This article aims to explore the importance of integrating environmental content into the Civic Education curriculum to build early environmental awareness. The research methods used include literature review, surveys, and direct observation in several elementary schools. The findings indicate that students who receive Civic Education with a focus on environmental issues possess a more positive understanding, attitude, and actions towards the environment. They are more likely to engage in conservation activities such as recycling and waste reduction. Additionally, this approach encourages students to develop critical thinking skills and creative solutions to environmental challenges. In conclusion, the integration of environmental education into Civic Education not only enhances the quality of education but also contributes to the formation of a generation that is more aware and concerned about the environment. Thus, environmentally-oriented Civic Education teaching is a crucial step in creating a more sustainable society.